L’université des artistes ou comment utiliser la forme artistique pour former les professeurs - Séverine Colinet (Université de Provence, 2020)
Laicity in school is a "socially lively question" in the face of successive traumatic events that break into the school community. The training of both teachers and students is all the more complex: between the unsaid, reticence, fears and denial of emotions. The subjects experience the relationship to uniqueness in relation to their biographical background. Our research aims to present an engineering device anchored on the knowledge-relationship mobilizing the sensitive experience of the subjects. Eight biographical interviews conducted with students and teachers made it possible to evaluate the effects of the system on the subjects and their power to act on the basis of biographical research.